Long-Term Patency of Venous Conduits Targeting the Right Coronary Artery System—Single Is Superior to Sequential bypass Grafting - Rawa Arif; Aglaia Warninck; Mina Farag; Wiebke Sommer; Florian Leuschner; Norbert Frey; Matthias Karck; Gregor Warnecke; Nicolas A. Geis (Journal of Cardiovascular Development and Disease, 2022)
Objective: Little is known about the fate of bypass grafts to the right coronary system. To investigate the long-term patency of venous bypass grafts directed to the right coronary artery (RCA) based on postoperative angiograms and to identify predictors of graft occlusion. Methods: In this single-center study, all patients who underwent coronary angiography from 2005 to 2021 after previously undergoing isolated coronary artery bypass grafting (CABG) were included. The primary endpoint was graft occlusion over a median follow-up of 9.1 years. Results: Among a total of 1106 patients (17.0% women, 64 (57–71) years median age), 289 (26.1%) received a sequential vein graft and 798 (72.2%) a single graft. Multivariate regression revealed age (HR 1.019, CI 95% 1.007–1.032), the urgency of CABG (HR 1.355, CI 95% 1.108–1.656), and severely impaired left ventricular function (HR 1.883, CI 95% 1.290–2.748), but not gender and chronic total occlusion (CTO) as predictive factors for graft occlusion. Single conduits were found to be a predictor of graft patency (HR 0.575 CI 95% 0.449–0.737). The angiographic outcome showed an overall 10-year freedom from graft occlusion of 73.4% ± 1.6%. The 5-year (10-year) freedom from graft occlusion was 76.9% ± 2.8% (57.8% ± 4.0%) for sequential grafts and 90.4% ± 1.1% (77.8% ± 1.7%) for single grafts (log-rank p < 0.001). Conclusions: In symptomatic patients with renewed angiography, venous bypass grafting of the RCA showed acceptable long-term patency rates. Single bypass grafting of the RCA was superior to sequential grafting, which needs to be further investigated.